Optical strain sensor based on FPI micro-cavities produced by the fiber fuse effect - Fatima Domingues, M. (2017)
In this work we present a cost effective strain sensor based on micro-cavities produced through the re-use of optical fibers destroyed by the catastrophic fuse effect. The strain sensor estimated sensitivity is 2.22 +/- 0.08 pm/mu epsilon. After the fuse effect, the damaged fiber becomes useless and, consequently, it is an economical solution for sensing proposes, when compared with the cavities produced using other complex methods. Also, the low thermal sensitivity is of great interest in several practical applications, allowing eluding cross-sensitivity with less instrumentation, and consequently less cost.